The regulation of dividends in terms of companies Act 71 of 2008: can a company distribute disproportionate dividends to shareholders of the same class of shares? - Nhlapho, Thandiwe (My University, 2018)
This report critically analyses the current regulation of dividends in South Africa with a specific reference to disproportionate dividends. The Companies Act 71 of 2008 (the ‘Companies Act’) does not expressly provide for disproportionate dividends. There is equally no prohibition on declaring and distributing disproportionate dividends. The law is therefore unsettled as far as disproportionate dividends are concerned. The uncertainty requires clarification either through legislative intervention or judicial determination. The report proposes solutions to circumstances under which it is inevitable to distribute proportionate dividends to holders of shares of the same class. I argue that treating shares of the same class dissimilarly should be permitted to the extent that it is justifiable in order to achieve economic results and growth in the company. Furthermore, I recommend possible amendments to the Companies Act. Lastly, the report examines the liability for declaring dividends contrary to the Companies Act. To add a comparative perspective, I make reference to the laws in foreign jurisdictions such as, New Zealand and the United States of America. In addition, the position under the Model Business Corporation Act will be observed.
Submitted in partial fulfillment of the requirements for the degree of Master of Laws (by Coursework and Research Report) at the University of the Witwatersrand, Johannesburg 2018
Keywords: Corporation law--South Africa; Minority stockholders--South Africa